Proceedings of SPE International Symposium on Oilfield Chemistry 2005
DOI: 10.2523/93254-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Transport in Porous Media of New Water Shutoff / Conformance Control Microgels

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe performances of new microgels specifically designed for water shutoff and conformance control were extensively investigated at laboratory scale. These microgels are preformed, stable, fully water soluble, size controlled with a narrow size distribution, and non-toxic. They reduce water permeability by forming adsorbed layers soft enough to be very easily collapsed by oil-water capillary pressure, so that oil permeability is not significantly affected. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Zaitoun et al insisted that relatively large microgel size results in low amount of microgel penetration of low-permeability zones [22]. Several authors suggested and explained the disproportionate permeability reduction (DPR) effects or sometimes called relative permeability modification (RPM) effects [11,[23][24][25][26]. According to DPR, it reduces relative water permeability dominantly rather than relative oil permeability, even if gel solution penetrates both low-and highpermeability zones.…”
Section: Basic Theoriesmentioning
confidence: 99%
“…Zaitoun et al insisted that relatively large microgel size results in low amount of microgel penetration of low-permeability zones [22]. Several authors suggested and explained the disproportionate permeability reduction (DPR) effects or sometimes called relative permeability modification (RPM) effects [11,[23][24][25][26]. According to DPR, it reduces relative water permeability dominantly rather than relative oil permeability, even if gel solution penetrates both low-and highpermeability zones.…”
Section: Basic Theoriesmentioning
confidence: 99%
“…If gelation is stopped sufficiently early or if gels are sufficiently sheared so that gel particles remain significantly smaller than pore throats, the gel suspensions can propagate through porous rock; however, the level of mobility reduction (residual resistance factor) is generally small (less than 2). 16 Independent studies at several locations (the University of Kansas, 125,126,155 the University of TX, 124 New Mexico Tech, 156,157 Stavanger College, 128 and BP 127 ) confirm that aluminum-citrate-HPAM gelants and gels behave like other gelants and gels.…”
Section: Are Colloidal Dispersion Gels Reallymentioning
confidence: 99%
“…The lowest F rro value was 1.2. We found five cases where gels provided water residual resistance factors greater than 2,100 and ultimate F rro values of 2 or less (see Entries 7,8,10,11,and 16 in Tables 1 and 2). These cases used gels with 0.3% to 0.5% HPAM.…”
Section: Permeability To Oil After Gel Placementmentioning
confidence: 99%
See 2 more Smart Citations